The Savvy Survey #6e: Understanding How Question Type Impacts Future Analysis - Colleen E. Gariton; Glenn D. Israel (EDIS)
This publication will briefly look at how the intent of a survey affects which types of questions should be asked and how the data can be analyzed to help address this intent. It is intended to provide guidance to Extension professionals, as well as persons in community organizations, who conduct surveys for program planning, improvement, and evaluation. Written by Colleen E. Gariton and Glenn D. Israel, and published by the UF/IFAS Department of Agricultural Education and Communication. https://edis.ifas.ufl.edu/pd083